Analysis of Contoured Anatomic Plate Fixation versus Intramedullary Rod Fixation for Acute Midshaft Clavicle Fractures. (1st March 2014) - Kwak-Lee, Juliann; Ahlmann, Elke R.; Wang, Lingjun; Itamura, John M.
Abstract : The recent trend has been toward surgical fixation of displaced clavicle fractures. Several fixation techniques have been reported yet it is unclear which is preferable. We retrospectively reviewed one hundred one consecutive patients with acute midshaft clavicle fractures treated operatively at a level-1 trauma center. Thirty-four patients underwent intramedullary pin fixation and 67 had anatomic plate fixation. The outcomes we assessed were operative time, complications, infection, implant failure, fracture union, range of motion, and reoperation rate. There were 92 males and 9 females with an average age of 30 years (range: 14–68 years). All patients were followed to healing with an average followup of 20 months (range: 15–32 months). While fracture union by six months( P = 0.8729 ) and range of motion at three months( P = 0.6139 ) were similar, the overall healing time for pin fixation was shorter( P = 0.0380 ) . The pin group had more infections( P = 0.0335 ) and implant failures( P = 0.0245 ) than the plate group. Intramedullary pin fixation may have improved early results, but there was no long term difference in overall rate of union and achievement of full shoulder motion. The higher rate of implant failure with pin fixation may indicate that not all fracture patterns are amenable to fixation using this device.